B-mode ultrasound and dynamic contrast-enhanced ultrasound (DCE-US) of the bowel wall in patients with gastrointestinal food allergy in comparison to Crohn's disease and healthy controls - Wildner, Dane; Raithel, Martin; Waldner, Maximilian J; Hagel, Alexander F.; Neurath, Markus F; Pfeifer, Lukas (Ultrasound International Open, 2025)
The aim of this study was to assess bowel wall thickness using B-mode ultrasound (US) and perfusion measurement by DCE-US in patients with a food allergy (FA) compared to healthy controls (HCs) and patients with active Crohn's disease (CD).Bowel wall thickness and perfusion were assessed in FA patients as well as in HCs on a potato rice diet (PRD) and after a provocation diet (PD). Additionally, patients with active CD were examined for further comparison. A total of 48 individuals (20 with FAs, 20 with CD, and 8 HCs) were included. There was no significant difference between the HCs and patients with FAs regarding the thickness of the terminal ileum (1.8mm vs. 2.2mm; p=0.46) and the sigmoid colon (2.1mm vs. 2.1mm; p=1) on a PRD. After a PD, the median value was significantly lower in the terminal ileum for HCs compared to patients with FAs (1.6 mm vs. 2.3 mm; p=0.03). In CD patients, the thickness of the terminal ileum was far more pronounced (median thickness 6 mm) compared to HCs and patients with FAs (p<0.001). There was no statistically significant difference for all tested DCE-US parameters in the terminal ileum between the HCs and patients with FAs on either PRD or PD. However, DCE-US perfusion parameters (PE, WiAUC, WiR, WiPi, and WoR) were significantly higher in patients with CD compared to HCs and patients with FAs on a PD. Assessment of wall thickening of the terminal ileum using US and perfusion measurements via DCE-US appears to be insufficient for distinguishing between HCs and patients with FAs. However, US and DCE-US could be helpful in differentiating patients with CD from those with FAs.
Keywords: food allergy; Crohn’s disease; DCE-US; bowel ultrasound; dynamic contrast-enhanced ultrasound